Timbulan dan Komposisi Sampah Bahan Berbahaya Dan Beracun (B3) Sarana Pelayanan Kota Di Kota Padang - Yenni Ruslinda; Ade Supratman; Nur Indah Lestari (Jurnal Dampak, 2019)
Generation and composition data of solid waste was the initial data needed in solid waste management system planning. This research aims to measure and analyze the generation and composition of Hazardous Solid Waste (HSW) from the source of municipal service facilities in Padang City. Municipal service facilities studied include recreation facilities, beaches, parks, and roads. Determination of the number of samples based on SNI 19-3964-1994 with the total sample of 11 samples and confidence level of 99.77%. Results of the study showed that total HHW generation from municipal service facilities in Padang city was 394.67 kg/day (2,312.41 liters/day), with the generation average of 0.000220 kg/m2/day in weight basis or 0.001262 liters/m2/day in volume basis. The percentage of HHW generation to total solid waste of municipal service facilities in Padang City was 0.95% in weight basis or 0.61% in volume basis. The largest composition of HHW from municipal service sources based on the type of use was body care products by 84% and based on general characteristics is toxic by 87%.Keywords: Composition, Generation, Hazardous Solid Waste (HSW), Municipal service facilitiesABSTRAKData timbulan dan komposisi sampah merupakan data awal yang dibutuhkan dalam perencanaan sistem pengelolaan sampah. Penelitian ini bertujuan untuk mengukur dan menganalisis timbulan dan komposisi sampah B3 yang berasal dari sarana pelayanan di Kota Padang. Sarana pelayanan kota dalam penelitian ini meliputi sarana rekreasi, pantai, taman, dan penyapuan jalan. Penentuan jumlah sampel berdasarkan SNI 19-3964-1994, dengan jumlah sampel sebanyak 11 buah dan tingkat kepercayaan 99,77%. Dari hasil penelitian diperoleh timbulan sampah B3 dari sarana palayanan di Kota Padang sebesar 394.67 kg/hari (2,312.41 liter/hari) dengan satuan timbulan rata-rata 0,000220 kg/m2/hari dalam satuan berat atau 0,001262 liter/m2/hari dalam satuan volume. Persentase timbulan sampah B3 di dalam total sampah pelayanan kota di Kota Padang adalah 0,95% dalam satuan berat atau 0,61% dalam satuan volume. Komposisi sampah B3 terbesar dari sumber pelayanan kota berdasarkan jenis penggunaannya merupakan produk perawatan badan sebesar 84% dan berdasarkan karakteristiknya bersifat toksik sebesar 87%.Kata kunci: Komposisi, Timbulan, B3, Sumber pelayanan kota